Ventricular arrhythmia risk is associated with myocardial scar but not with response to cardiac resynchronization therapy. Issue 9 (8th September 2020) - Linhart, Markus; Doltra, Adelina; Acosta, Juan; Borràs, Roger; Jáuregui, Beatriz; Fernández-Armenta, Juan; Anguera, Ignasi; Bisbal, Felipe; Martí-Almor, Julio; Tolosana, Jose M; Penela, Diego; Soto-Iglesias, David; et al.
Abstract: Aims: Sudden cardiac death (SCD) risk estimation in patients referred for cardiac resynchronization therapy (CRT) remains a challenge. By CRT-mediated improvement of left ventricular ejection fraction (LVEF), many patients loose indication for primary prevention implantable cardioverter-defibrillator (ICD). Increasing evidence shows the importance of myocardial scar for risk prediction. The aim of this study was to investigate the prognostic impact of myocardial scar depending on the echocardiographic response in patients undergoing CRT. Methods and results: Patients with indication for CRT were prospectively enrolled. Decision about ICD or pacemaker implantation was based on clinical criteria. All patients underwent delayed-enhancement cardiac magnetic resonance imaging. Median follow-up duration was 45 (24–75) months. Primary outcome was a composite of sustained ventricular arrhythmia, appropriate ICD therapy, or SCD. A total of 218 patients with LVEF 25.5 ± 6.6% were analysed [158 (73%) male, 64.9 ± 10.7 years]. Myocardial scar was observed in 73 patients with ischaemic cardiomyopathy (ICM) (95% of ICM patients); in 62 with non-ischaemic cardiomyopathy (45% of these patients); and in all but 1 of 36 (17%) patients who reached the primary outcome. Myocardial scar was the only significant predictor of primary outcome [odds ratio 27.7 (3.8–202.7)], independent of echocardiographic CRT response. A total of 55 (25%) patients died from any cause or received heart transplant. For overall survival, only a combination of the absence of myocardial scar with CRT response was associated with favourable outcome. Conclusion: Malignant arrhythmic events and SCD depend on the presence of myocardial scar but not on CRT response. All-cause mortality improved only with the combined absence of myocardial scar and CRT response. Graphical Abstract: